Twelve tips for the recruitment and retention of general practitioners as teachers of medical students. (4th March 2018) - Alberti, Hugh; Atkinson, Jane
Abstract: Background: Primary care physicians have become a fundamental aspect of teaching in modern medical school curricula worldwide with a significant proportion of undergraduate teaching taking place in primary care. There are calls for this to increase with more patient care occurring in the community but teaching capacity in primary care is a potential challenge. Medical schools, therefore, need strategies to be able to increase their primary care physician teaching workforce. Methodology: We asked all Heads of General Practice Teaching in UK medical schools to share their three top tips for recruiting and retaining GPs to teach undergraduate students. The majority (two-thirds) of medical schools responded and we have summarized the answers into the following twelve tips. Results: Although the twelve tips are varied and comprehensive, including broad topics such as finances and training, one clear theme running through the majority of tips is good communication and relationships between education teams and GPs. Conclusions: The solutions to recruiting and retaining GPs to teach undergraduate medical students are clearly multifactorial and complex. We hope that by presenting suggestions from UK GP heads of teaching as these twelve tips provides some helpful, thought-provoking ideas and inspiration for both the UK and internationally.